eCM 2012
DOI: 10.22203/ecm.v023a27
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid-functionalised titanium as a superior surface for supporting human osteoblast (MG63) maturation

Abstract: Covalent modifications of titanium with small molecules known to promote human osteoblast maturation are especially attractive in developing superior biomaterials. An important step in securing competent bone formation at implant sites is promoting the formation of mature osteoblasts, either from committed pre-osteoblasts or from their mesenchymal progenitors. To this end our research has focussed on identifying molecules that enhance human osteoblast formation and maturation and to develop ways of covalently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…What remains to be determined is whether 24R,25D can promote hOB maturation when co-administered with agents known to synergistically co-operate with 1,25D; it is becoming clear that 1,25D often needs to interact with other factors to prosecute the desired response in target cells [13]. In our hands we consistently find that hOBs do not mobilise alkaline phosphatase (ALP) when treated with 1,25D in a serum-free in vitro setting and will only do so when the cells are in receipt of both 1,25D and certain growth factors such as epidermal growth factor [14], lysophosphatidic acid (LPA) or certain LPA receptor selective agonists [15][16][17][18]. Whilst a significant body of work is emerging on the role of LPA in osteoblast, and indeed skeletal biology in general, we will not expand on those areas here.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…What remains to be determined is whether 24R,25D can promote hOB maturation when co-administered with agents known to synergistically co-operate with 1,25D; it is becoming clear that 1,25D often needs to interact with other factors to prosecute the desired response in target cells [13]. In our hands we consistently find that hOBs do not mobilise alkaline phosphatase (ALP) when treated with 1,25D in a serum-free in vitro setting and will only do so when the cells are in receipt of both 1,25D and certain growth factors such as epidermal growth factor [14], lysophosphatidic acid (LPA) or certain LPA receptor selective agonists [15][16][17][18]. Whilst a significant body of work is emerging on the role of LPA in osteoblast, and indeed skeletal biology in general, we will not expand on those areas here.…”
Section: Introductionmentioning
confidence: 85%
“…The treatment of cells to quantify ALP activity was similar to that described by us recently [17]. Briefly, the MTS/PMS reagent was removed and the monolayers incubated for a further 15 min in fresh phenol red-free DMEM/ F12 to remove the residual formazan.…”
Section: Total Alp Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the hydrogel-based systems that have been investigated for cell survival and therapeutic angiogenesis are only mildly osteoinductive, we have shown that the addition of mineralized PLGA microspheres to fibrin gels further enhances osteogenic differentiation 113 ; such a system would allow for similar physical entrapment of LPA and presentation. Alternately, other groups are pursuing the covalent attachment of LPA to titanium constructs with the goal of stimulating osteoblast maturation and osseointegration 114 on scaffolds better suited to load-bearing applications. Given the pro-angiogenic and pro-arteriogenic nature of S1P, exogenous delivery has also been used in approaches for enhancing tissue-engineered bone regeneration.…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…In ascertaining the stability of our lysophosphatidate-functionalised Ti materials [2][3] to bone insertion, recovered and non-inserted functionalised controls were seeded with MG63 osteoblasts, cultured under conventional conditions for three days, and an assessment of cellular maturation determined via TNSALP activity assay. To our surprise we unexpectedly found that inserted, lysophosphatidate-functionalised dental implants were associated with the greatest TNSALP activity (~9 times greater) compared to irrigated, non-inserted, functionalised controls.…”
Section: Introductionmentioning
confidence: 99%